Reusable learning objects in healthcare education - Windle, Richard; Wharrad, Heather (IGI Global, 2010)
This chapter will review the definition, development and characteristics of reusable learning objects (RLOs) and outline examples of how these resources are meeting the challenges of interprofessional learning. It will discuss the ways in which pedagogy is developed and expressed within RLOs and how this may impact on interprofessionality.